2021
DOI: 10.1016/j.mpdhp.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology features of the lung in COVID-19 patients

Abstract: COVID-19 is the infectious disease caused by the recently discovered coronavirus, SARS-CoV-2, unknown before the outbreak in Wuhan, China, in December 2019. COVID-19 is a pandemic, infectious disease that has simultaneously affected many countries globally. The leading cause of dead in patients with COVID-19 is hypoxic respiratory failure from acute respiratory distress syndrome (ARDS). Diffuse alveolar damage (DAD) is the histopathological pattern commonly described in all the postmortem series up to date. DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
1
31
0
2
Order By: Relevance
“…Besides, histopathological investigation of the lungs and brain showed that COVID-19 patients could experience various pulmonary injuries and tissue damage in the brain [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, histopathological investigation of the lungs and brain showed that COVID-19 patients could experience various pulmonary injuries and tissue damage in the brain [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an ongoing discussion about the specificity of these changes as DAD seen in other viral infections show similar features. [7] …”
Section: Discussionmentioning
confidence: 99%
“…[2] , While some have studied autopsy findings in decedents who succumbed to the virus in the community, others have simply focused on pathologic findings from the lungs of decedents who were treated for the infection and those who had lobectomy for cancer and later found out to be COVID-19 positive. [3] , [4] , [5] , [6] , [7] , [8] Large multicentric study by Hooper et al summarised finding from survey of 135 autopsies in a multi-institutional setting and detailed the frequency of co-morbidities in the subjects. [9]…”
Section: Introductionmentioning
confidence: 99%
“…During the first week after pulmonary injury, the acute/exudative phase, intra-alveolar oedema, and interstitial widening are evident along with diffuse or focal hyaline membranes. Inflammation is generally low during this phase and thrombi may be present [ 100 ]. The subsequent, second phase of DAD is known as the organising/proliferative phase, which is characterised by cellular fibroblastic proliferation.…”
Section: Lung Pathology Of Highly Pathogenic Hcov Infectionsmentioning
confidence: 99%
“…Following the organising phase, patients can either experience a gradual resolution of DAD or develop interstitial fibrosis. Regardless, most survivors experience some kind of functional impairment of the lungs [ 100 ].…”
Section: Lung Pathology Of Highly Pathogenic Hcov Infectionsmentioning
confidence: 99%